The Meaning of Dukhan and Wardatan Ka-ddihan in Surah Ad-Dukhan (10-11) and Surah Ar-Rahman (37): A Scientific Thematic Study - Habibullah, Ilham; Anggara, Deki Ridho Adi; Rifaannudin, Mahmud; Pratiwi, Utari Nur (Universitas Muhammadiyah Surakarta, 2025)
This study examines the Quranic terms